Experimental study of slender LCFST columns connected by steel linking plates. (December 2016) - Xu, Minyang; Zhou, Ting; Chen, Zhihua; Li, Yanbo; Bisby, Luke
Abstract: This paper presents the results of an experimental investigation of L-shaped columns composed of concrete-filled steel tubes (LCFST columns) connected by steel linking plates. As a new kind of composite column, the fundamental structural behavior of LCFST columns connected by steel linking plates is discussed in this paper. Eight large-scale LCFST columns were constructed and loaded under either concentric axial compression or biaxial eccentric compression up to failure. Slenderness ratio, thickness of the steel linking plates and load eccentricities were all studied within the experimental program. The relationships of load versus longitudinal displacement, lateral deflection at mid-height, longitudinal strain at mid-height etc. are presented. It is demonstrated that specimens with larger slenderness ratios or eccentricities have lower ultimate load capacities, as expected. It is also demonstrated that the steel connection plates, also as expected, have a considerable influence on confining lateral deflections of the mono CFST columns and that they significantly contribute to the columns' ultimate carrying capacity. Predictive formulas for calculating the ultimate loads of LCFST columns connected by steel linking plates are proposed based on modifications of the ANSI/AISC 360-05 guidelines. Graphical abstract: L-shaped columns composed of concrete-filled steel tubes (LCFST columns) connected by steel linking plates in residential buildings in Cangzhou, China and the test specimen in the paper. Highlights: Specimens with larger slenderness ratios or eccentricities have smaller ultimate loads. Ultimate loads of specimens rise with thickness of steel linking plates increased. Directions of principal strains in steel linking plates are almost horizontal and vertical. Predictive formulas are reasonable for designing the specimens.